(untitled) (Progressive Agriculture, 2013)
In Bangladesh the majority of the population, particularly the rural people are poverty stricken. This study assesses the possibility of addressing poverty through an advanced technology of broiler rearing model which ensures high participation of rural women, protects the environment and secures from harmful or unnecessary residual effects on human health. Bangladesh Rural Enterprise and Agricultural Project-II (BREAD-II) of Winrock International, a non-profit organization has introduced this model. The present study focuses on the impact of this model on rural household income through comparing profitability of broiler farms adopting this model compared to those of non-adopters. This comparative study confirmed higher profit of BREAD-II Model of broiler rearing which eventually indicates that it can be considered as an effective tool for poverty alleviation. DOI: http://dx.doi.org/10.3329/pa.v19i1.17365 Progress. Agric. 19(1): 143 - 153, 2008